2022
DOI: 10.1111/gfs.12583
|View full text |Cite
|
Sign up to set email alerts
|

Drought stress impact on the performance of deep convolutional neural networks for weed detection in Bahiagrass

Abstract: Machine vision‐based weed detection relies on features such as plant colour, leaf texture, shape, and patterns. Drought stress in plants can alter leaf colour and morphological features, which may in turn affect the reliability of machine vision‐based weed detection. The objective of this research was to evaluate the feasibility of using deep convolutional neural networks for the detection of Florida pusley (Richardia scabra L.) growing in drought stressed and unstressed bahiagrass (Paspalum natatum Flugge). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…This limitation may be overcome by increasing the number of training images. Zhuang et al [28] obtained similar low P and R values when using YOLOv3 for R. scabra detection in drought-stressed and unstressed turfgrasses. In this research, authors argued that high background variability in the training dataset increases cause a less efficient feature extraction and consequently decreases P and R metrics.…”
Section: Resultsmentioning
confidence: 81%
“…This limitation may be overcome by increasing the number of training images. Zhuang et al [28] obtained similar low P and R values when using YOLOv3 for R. scabra detection in drought-stressed and unstressed turfgrasses. In this research, authors argued that high background variability in the training dataset increases cause a less efficient feature extraction and consequently decreases P and R metrics.…”
Section: Resultsmentioning
confidence: 81%
“…Previous research 50 has demonstrated that increasing the number of training images has a positive impact on the performance of neural networks, resulting in higher accuracy values approaching 1. Consequently, as the number of training images increased, the comparative improvement of SSL methods over the FSL wileyonlinelibrary.com/journal/ps model diminished.…”
Section: Resultsmentioning
confidence: 99%
“…2, each image block was assigned one of two labels: 'turf' or 'weed', with 'turf' representing the sub-images without weeds, whereas 'weed' representing the sub-images containing weeds. To evaluate the performance of the SSL method on varying numbers of labeled images, the labeled data were divided into four quantity levels (50,100,200, and 400 labels per class) per data set, as shown in Table 1. All data sets comprise training data with labels, unlabeled training data, validation data, and testing data.…”
Section: Data Set Preparationmentioning
confidence: 99%
“…Weed detection using machine vision relies on features, like plant color, leaf texture, shape and patterns. Drought stress can impact leaf color and morphological features in plants, potentially affecting the reliability of machine vision-based weed detection [89]. But they still lack universal segmentation capabilities for different crop varieties with varying leaf shapes and canopy structures.…”
Section: Biological Morphological Featuresmentioning
confidence: 99%